2020
DOI: 10.48550/arxiv.2008.08548
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Survey of Knowledge-based Sequential Decision Making under Uncertainty

Shiqi Zhang,
Mohan Sridharan

Abstract: Reasoning with declarative knowledge (RDK) and sequential decision-making (SDM) are two key research areas in artificial intelligence. RDK methods reason with declarative domain knowledge, including commonsense knowledge, that is either provided a priori or acquired over time, while SDM methods (probabilistic planning and reinforcement learning) seek to compute action policies that maximize the expected cumulative utility over a time horizon; both classes of methods reason in the presence of uncertainty. Despi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…This work aims to enable a robot to represent and reason with contextual information to guide robot planning under uncertainty. Researchers have developed algorithms that reason with contextual knowledge to guide sequential decision making [11]. The contextual knowledge can be in a variety of forms, such as commonsense knowledge [12], action knowledge [13], [14], and graph-based knowledge [7], [15].…”
Section: Related Workmentioning
confidence: 99%
“…This work aims to enable a robot to represent and reason with contextual information to guide robot planning under uncertainty. Researchers have developed algorithms that reason with contextual knowledge to guide sequential decision making [11]. The contextual knowledge can be in a variety of forms, such as commonsense knowledge [12], action knowledge [13], [14], and graph-based knowledge [7], [15].…”
Section: Related Workmentioning
confidence: 99%
“…In a different direction, exploiting declarative knowledge to construct actions sequences can also help reward shaping to find the optimal policy, as a few studies [118,119] have demonstrated. We refer to the survey by [122] for further examples of studies both in probabilistic planning and RL aiming to reason with declarative domain knowledge.…”
Section: Hierarchical Approachesmentioning
confidence: 99%